2017
DOI: 10.24171/j.phrp.2017.8.5.09
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Tuberculosis Treatment: Evidence from Iran's Health System

Abstract: ObjectivesThis study aimed to estimate the cost of smear-positive drug-susceptible pulmonary tuberculosis (TB) treatment of the patients in the Azadshahr district, Golestan Province, Iran.MethodsIn this retrospective study, all new smear positive pulmonary TB patients who had been registered at the district’s health network between April, 2013 and December, 2015 and had successfully completed their treatment were entered into the study (45 patients). Treatment costs were estimated from the provider’s perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…29 The total cost of treating a new smear-positive pulmonary TB patient in Iran was USD 1,409 which was split into direct and indirect costs (USD 1,226.00 and USD 183.00) respectively but these figures were three times more than our median costs. 30…”
Section: Discussionmentioning
confidence: 99%
“…29 The total cost of treating a new smear-positive pulmonary TB patient in Iran was USD 1,409 which was split into direct and indirect costs (USD 1,226.00 and USD 183.00) respectively but these figures were three times more than our median costs. 30…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sputum smear-negative TB (SSNTB) are less infectious than patients with sputum smear-positive TB (SSPTB) [ 7 ]. A new detected SSPTB patient costs US$ 1409 for the Iranian health system [ 8 ]. A systematic review and meta-analysis in 2019 showed that health care workers residing in the northern and the western regions of the country had the highest prevalence of latent TB, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of tuberculosis is about 365 cases per 100,000 people in Africa; it is about 5 people per 100,000 people in London; it is about 21 people per 100,000 people in Spain; it is 5 people per 100,000 people in America; and globally, on average, it is 13 cases per 100,000 people. In Iran, the incidence rate of tuberculosis reached 16 cases per 100,000 people in 2015 and declined to 14 cases per 100,000 people in 2016 and 2017, and fell to 13 cases per 100,000 people in 2020, where 4% of cases of tuberculosis patients were under 14 years old [ 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%